UNIT 9.49 Measurement and Characterization of Apoptosis by Flow Cytometry. Issue 1 (1st July 2016) - Telford, William; Tamul, Karen; Bradford, Jolene
Abstract : Apoptosis is an important mechanism in cell biology, playing a critical regulatory role in virtually every organ system. It has been particularly well characterized in the immune system, with roles ranging from immature immune cell development and selection to down‐regulation of the mature immune response. Apoptosis is also the primary mechanism of action of anti‐cancer drugs. Flow cytometry has been the method of choice for analyzing apoptosis in suspension cells for more than 25 years. Numerous assays have been devised to measure both the earliest and latest steps in the apoptotic process, from the earliest signal‐transduction events to the late morphological changes in cell shape and granularity, proteolysis, and chromatin condensation. These assays are particularly powerful when combined into multicolor assays determining several apoptotic characteristics simultaneously. The multiparametric nature of flow cytometry makes this technology particularly suited to measuring apoptosis. In this unit, we will describe the four main techniques for analyzing caspase activity in apoptotic cells, combined with annexin V and cell permeability analysis. These relatively simple multiparametric assays are powerful techniques for assessing cell death. © 2016 by John Wiley & Sons, Inc.